Plant polysaccharides used as immunostimulants enhance innate immune response and disease resistance against Aeromonas hydrophila infection in fish. (December 2016) - Wang, Erlong; Chen, Xia; Wang, Kaiyu; Wang, Jun; Chen, Defang; Geng, Yi; Lai, Weimin; Wei, Xianchao
Abstract: Plant polysaccharides (PPS) are an important medicinal plant product, and play a major role in preventing and controlling infectious microbes in aquaculture. The present study investigated the effect of three PPS; Ficus carica polysaccharides (FCPS), Radix isatidis polysaccharides (RIPS), and Schisandra chinensis polysaccharides (SCPS), used as feed additives, on innate immune responses and disease resistance against Aeromonas hydrophila in crucian carp. Results show that crucian carp fed with these PPS showed significant (p < 0.05) enhancement of their innate immune response including leukocyte phagocytosis activity, serum bactericidal activity, lysozyme activity, total protein level, complement C3, and superoxide dismutase activity compared with the control group. Their degree of influence on these immune parameters was in the order of FCPS > RIPS > SCPS, except for lysozyme activity (RIPS > FCPS > SCPS). In addition, fish cumulative mortalities in the three treatment groups were remarkably lower than in the control group (95%) when challenged with A. hydrophila, relative percent survivals were 57.9%, 47.4%, and 42.1% in FCPS, RIPS, and SCPS groups, respectively. These results suggest that FCPS, RIPS, and SCPS used as immunostimulants are capable of enhancing immune responses and disease resistance against A. hydrophila in crucian carp, and that FCPS was the most effective. The findings from this study will help accelerate research of this topic, and promote the application and development of immunostimulants, such as Chinese herbs, in aquaculture. Graphical abstract: Highlights: FCPS, RIPS and SCPS were successfully extracted and purified with high contents. Three PPS used as feed additives enhance innate immune response in crucian carp. Three PPS used as feed additives enhance disease resistance against A. hydrophila. FCPS, RIPS and SCPS conferred RPS with 57.9%, 47.4% and 42.1%, respectively.